Cultivating Rice (Oryza sativa L.) with Urban Waste Compost – A Scientific Study - Joseph, B.; Gouthami, B.; Prathiksha, G. Jaya; Reddy, N. Ramohan; Reddy, A. Raja (Chronicle of Bioresource Management, 2023)
A field experiment was conducted to study the impact of urban waste compost (UWC) on rice (Oryza sativa L.)at College Farm, School of Agricultural Sciences, Mallareddy University, Maisammaguda, Hyderabad, Telangana state during Rabi, 2020–21. Two treatments (T1: RDF and T2: RDF+ UWC 28 t ha-1) have been imposed to study the yield and yield attributes of Chintu variety of rice crop. The results revealed that rice crop treated with RDF+UWC (T2) produced maximum number of tillers (265 m-2) and total dry matter (80.10 g plant-1), thus, higher grain yield (5250 kg ha-1) as compared to that of untreated plot (T1: RDF alone) (194 tillers m-2, 73.68 g plant-1, 4125 kg ha-1). Further, the same treatment recorded higher gross (Rs. 1,20,750 ha-1) and net returns (Rs. 75,406 ha-1) and B:C ratio (2.66) vis-a-vis untreated plot (Rs. 50,644 ha-1;2.14).